PERISTIWA MANGKOK MERAH DI KALIMANTAN BARAT TAHUN 1967 - Superman Superman (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2017)
The involvement of a handful of Chinese society in the political movement around 1963 in West Kalimantan is an interesting thing to study. They assembled in PGRS-Paraku organization which was originally an opposition movement to launch “Ganyang  Malaysia”. But when the political map in Indonesia changed, PGRS-Paraku later declared a forbidden organization to be suppressed. This gave rise to a great conflict between Dayak and Chinese Communists. The Chinese that not a communist in land face of the impact. They had evacuated to safe places, especially in Singkawang. This incident resulted in the refugees have to start their lives over again due to leave their lives in the inland is sufficient before.